5
$\begingroup$

I recently came across this problem, although trivial to compute by hand - is a little challenging for me to interpret. Notably, we have three matrices:

$$\vec{c}= \begin{bmatrix} 0.5 \\ 0.5 \end{bmatrix},\hspace{0.2in} \vec{x}= \begin{bmatrix} 2 \\ 3 \end{bmatrix},\hspace{0.2in} \vec{\mu}= \begin{bmatrix} 1 \\ 2 \end{bmatrix}, \hspace{0.2in} \mathbf{\Sigma} = \begin{bmatrix} 2 & 1 \\ 1 & 4 \end{bmatrix} $$

We then have the following calculation, which I have solved below.

$\vec{c}^{\,T}(\vec{x}-\vec{\mu}) (\vec{c}^{\ T}\mathbf{\Sigma}\vec{c})^{-1}$ ${}=\begin{bmatrix} \ 0.5 \end{bmatrix}$

The calculation is trivial. However, how do I interpret this solution - assuming $\vec{x}$ is a data vector, $\vec{\mu}$ is a mean vector, and $\mathbf{\Sigma}$ is a covariance matrix?

$\endgroup$
  • 1
    $\begingroup$ Hint: think of standardization and consider the variance of $\vec{c}^\prime \vec{x}.$ $\endgroup$ – whuber Sep 11 '18 at 19:18
6
$\begingroup$

Consider the random variable $$y = c^T x$$Then the mean of $y$ is $$E(y) = c^T E(x) = c^T \mu$$ and variance of $y$ is $$var(y) = E(y - c^T \mu)^2 = E(y^2) - (c^T \mu)^2 = E(y^2) + c^T \mu\mu^T c \tag{*}$$ But $$y^2 = (c^Tx)^2 = c^Tx c^Tx= c^Txx^Tc$$ So $$E(y^2) = c^TE(xx^T)c = c^T(\Sigma - \mu\mu^T)c \tag{**}$$ Replace $(**)$ is $(*)$, we get $$var(y) = c^T\Sigma c$$ Let $z$ be a standard version of $y$, i.e. $$z = \frac{y - E(y)}{var(y)} = \frac{c^Tx - c^T\mu}{c^T\Sigma c} = c^T(x - \mu)(c^T\Sigma c)^{-1} $$ So, you have computed the $z$ here.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.